The Anatomical Basis of Paradoxical Masseteric Bulging after Botulinum Neurotoxin Type A Injection - Hyung-Jin Lee; In-Won Kang; Kyle K. Seo; You-Jin Choi; Seong-Taek Kim; Kyung-Seok Hu; Hee-Jin Kim (Toxins, 2016)
The aim of this study was to determine the detailed anatomical structures of the superficial part of the masseter and to elucidate the boundaries and locations of the deep tendon structure within the superficial part of the masseter. Forty-four hemifaces from Korean and Thai embalmed cadavers were used in this study. The deep tendon structure was located deep in the lower third of the superficial part of the masseter. It was observed in all specimens and was designated as a deep inferior tendon (DIT). The relationship between the masseter and DIT could be classified into three types according to the coverage pattern: Type A, in which areas IV and V were covered by the DIT (27%, 12/44); Type B, in which areas V and VI were covered by the DIT (23%, 10/44); and Type C, in which areas IV, V, and VI were covered by the DIT (50%, 22/44). The superficial part of the masseter consists of not only the muscle belly but also the deep tendon structure. Based on the results obtained in this morphological study, we recommend performing layer-by-layer retrograde injections into the superficial and deep muscle bellies of the masseter.